Role of Consortium in Academic Libraries: a case study of IISERs - Srivastava, Ruchi (International Journal of Scientific Research and Management (IJSRM), 2017)
With the information revolution brought about by the development of the World  Wide Web, libraries at every level have graduated from their traditional role as store houses of information to vigorous disseminators of information. This is necessary given the changing information seeking habits and spiraling expectations of users. Online periodicals have also encroached upon acquisitions budgets. Any library consortia often focuses on the benefits a member library expects to receive in return for its paid membership in a consortium. This paper discusses the need and role of consortia specially in academic libraries with special reference to Indian Institute of Science Education and Research established by MHRD to promote basic science education in India